Amadis of Gaul. a novel of chivalry of the 14th century presumably first written in Spanish - Rodríguez de Montalvo, Garci; Place, Edwin B. (Edwin Bray), 1891-; Behm, Herbert C. (Studies in Romance languages (Lexington, Ky.), 2015)
In the long history of European prose, few works have been more influential and popular than Amadis of Gaul. It is a landmark work among the knight-errantry tales and probably derives from an oral tradition. Although its original author is unknown, it was likely written during the early fourteenth century, with the first known version of this work, dating from 1508, written in Spanish by Garci Ordóñez (or Rodríguez) de Montalvo. An early bestseller of the age of printing, Amadis of Gaul was translated into dozens of languages and spawned sequels and imitators over the centuries. A handsome, va.